CONCEPTUALIZATION OF COMPETENCE AND COMPETENCY IN PEDAGOGICAL THEORY - Nozima Rasulova; Azizbek Mukhamedov, PhD (Western European Studies, 2025)
This study explores the multifaceted nature of professional competence for English language teachers, with a focus on integrating subject-specific expertise, pedagogical skills, digital literacy, and personal attributes to enhance teaching effectiveness in diverse educational contexts. Drawing on contemporary educational theories, including Channa et al. (2025), Rasulova (2024), and Markova’s model, professional competence is conceptualized as a dynamic, integrative framework encompassing special, social, personal, and individual competencies. The research highlights the growing importance of digital pedagogy, intercultural communicative competence, emotional intelligence, and reflective practice, particularly in the context of Uzbekistan’s educational reforms and global trends in teacher education. By synthesizing frameworks such as UNESCO’s ICT Competency Framework, the EU’s DigCompEdu, and CEFR standards, the study proposes a comprehensive digital platform to foster the holistic development of future English teachers. This platform emphasizes not only linguistic mastery and teaching methodologies but also adaptability, cultural responsiveness, and technological proficiency to meet 21st-century educational demands. The findings underscore the need for teacher training programs to support continuous professional growth through reflective, inclusive, and technology-enhanced practices, particularly in multilingual and multicultural settings.
Keywords: Teacher professional competence; English language teaching; digital pedagogy